Habitat Matters: Behavior and Activity of Round Goby (Neogobius melanostomus) at Different Substrates - Anna Dziubińska; Mariusz Sapota; Emilia Socha (Fishes)
This study focuses on the behavior of the Round Goby in relation to various types of hard substrates, which may be crucial in the context of the emergence of hydrotechnical structures in their habitat. The aim of this study was to determine the behavior and habitat preferences of the Round Goby in relation to specific types of hard substrates. Three types of substrates were used in the experiments: bare, colonized by benthic organisms, and rocky. Laboratory observations were conducted and divided into three variants, each with two cycles—daytime and nighttime. Each variant involved different combinations of two substrates. It was found that during the day, fish spent more time on vegetated substrates than on bare or rocky ones. At night, the opposite trend was observed. The lowest activity was recorded when the fish had a choice between bare and rocky substrates. The largest fish in the experiments changed their habitat most frequently, indicating that body size influences the activity level. However, no significant differences were found in either the time spent on specific substrates or the number of substrate changes. In addition, it was observed that the total length of Round Gobies did not affect their activity level.